HUBUNGAN USIA IBU, USIA KEHAMILAN DAN PARITAS DENGAN KEJADIAN KETUBAN PECAH DINI (KPD) - Yuriska Tiara Ningsih; Shandy Kusumawardhani; Syaflindawati Ramin (Jurnal Ilmiah Citra Kebidanan, 2025)
Premature Rupture of Membranes (PROM) poses serious risks to both mother and baby, as it can lead to infections caused by bacteria entering the uterus, increasing the risk of maternal and neonatal death, preterm birth, and birth defects. This study aimed to identify factors associated with the incidence of PROM at Bakti Timah Hospital, Pangkalpinang, in 2024. The research employed a descriptive-analytic design with a case-control approach (ratio 1:2) involving 120 samples, consisting of 40 mothers with PROM (total sampling) and 80 mothers without PROM (random sampling). Data were analyzed using the chi-square test. This research was conducted in June to July at Bakti Timun Hospital, Pangkalpinang. The results showed that factors significantly associated with PROM were maternal age (p=0.019; OR=0.244) This means that there is a relationship between the mother's age and the occurrence of premature rupture of membranes, gestational age (p=0.042; OR=8.778) This means there is a relationship between gestational age and the occurrence of premature rupture of membrane, and parity (p=0.000; OR=0.157) This means there is a relationship between parity and the occurrence of premature rupture of membranes. Occupation was not significantly associated (p=0.071; OR=3.028), with gestational age being the dominant factor. These findings are expected to serve as a reference for healthcare workers in early detection and prevention of PROM, as well as in improving comprehensive antenatal care for pregnant women.